Persistent Parental RNAi in the Beetle Tribolium castaneum Involves Maternal Transmission of Long Double‐Stranded RNA - Thorsten Horn; Kalin D. Narov; Kristen A. Panfilio (Advanced Genetics, 2022)
Abstract Parental RNA interference (pRNAi) is a powerful and widely used method for gene‐specific knockdown. Yet in insects its efficacy varies between species, and how the systemic response is transmitted from mother to offspring remains elusive. Using the beetle Tribolium castaneum, an RT‐qPCR strategy to distinguish the presence of double‐stranded RNA (dsRNA) from endogenous mRNA is reported. It is found that injected dsRNA is directly transmitted into the egg and persists throughout embryogenesis. Despite this depletion of dsRNA from the mother, it is shown that strong pRNAi can persist for months before waning at strain‐specific rates. In seeking the receptor proteins for cellular uptake of long dsRNA into the egg, a phylogenomics profiling approach of candidate proteins is also presented. A visualization strategy based on taxonomically hierarchical assessment of orthology clustering data to rapidly assess gene age and copy number changes, refined by sequence‐based evidence, is demonstrated. Repeated losses of SID‐1‐like channel proteins in the arthropods, including wholesale loss in the Heteroptera (true bugs), which are nonetheless highly sensitive to pRNAi, are thereby documented. Overall, practical considerations for insect pRNAi against a backdrop of outstanding questions on the molecular mechanism of dsRNA transmission for long‐term, systemic knockdown are elucidated.